2021
DOI: 10.1073/pnas.2015675118
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-like factor Cabut has cell cycle regulatory properties similar to E2F1

Abstract: Using a gain-of-function screen in Drosophila, we identified the Krüppel-like factor Cabut (Cbt) as a positive regulator of cell cycle gene expression and cell proliferation. Enforced cbt expression is sufficient to induce an extra cell division in the differentiating fly wing or eye, and also promotes intestinal stem cell divisions in the adult gut. Although inappropriate cell proliferation also results from forced expression of the E2f1 transcription factor or its target, Cyclin E, Cbt does not increase E2F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…Consistent with a previous report, progenitors are normally arrested in either G1 or G2 phase under physiological conditions ( Fig. 6 A ) ( 47 ). However, depletion of yun/Phb increased the fraction of progenitors in G1 and decreased the fraction in S and G2 phases, indicating that the Yun/PHB complex may regulate cell cycle progression in progenitors ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with a previous report, progenitors are normally arrested in either G1 or G2 phase under physiological conditions ( Fig. 6 A ) ( 47 ). However, depletion of yun/Phb increased the fraction of progenitors in G1 and decreased the fraction in S and G2 phases, indicating that the Yun/PHB complex may regulate cell cycle progression in progenitors ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…6 C and SI Appendix , Fig. S35 C ) ( 25 , 47 ). Overexpression of E2F1/Dp in yun/Phb -depleted progenitors significantly rescued the proliferation defects observed in yun/Phb -depleted intestines, respectively, with esg ts > E2F1, yun/Phb RNAi intestines resembling esg ts > E2F1 intestines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Kruppel‐like factors (KLFs) are a set of transcription factors (TFs) involved in the regulation of many basic biological processes such as stem cell biology, cancer biology, and vascular biology (Cao, 2022b; García‐Niño & Zazueta, 2021; Oishi & Manabe, 2018). In intestines, recent studies revealed that KLFs may be involved in intestinal regeneration (Chen et al, 2020) and maintenance of normal function of intestinal stem cells (Wu et al, 2018; Wu, Sun, et al, 2021; Zhang et al, 2021), indicating that KLFs are crucial regulators for gut biology. Interestingly, recent studies showed that NPs even at non‐cytotoxic concentrations could modulate the expression of KLFs in different models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other factors are capable of controlling expression of the genes required for DNA replication, at least partly redundantly with the E2f complex. Several transcription factors have been described which have overlapping targets with E2f/Dp, including DREF and, recently, the SP/Krüppel-like factor Cabut (Cbt) ( Tue et al., 2017 ; Zhang et al., 2021 ). Intriguingly, Cbt can drive PCNA expression, consistent with our observation that PCNA-GFP is reduced but not absent upon Dp loss of function ( Figures 2 E and S1 D–S1F).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, continued proliferation and expression of replication genes in the absence of E2f1/Dp could be due either to de-repression from a lack of E2f repressive activity, or to active regulation by other factors such as Cbt. Nonetheless, since Cbt does not drive CycE expression ( Zhang et al., 2021 ), it seems likely that a combination of regulators of replication genes together with specific regulators of CycE are required to promote cell-cycle entry and progression in CySCs.…”
Section: Discussionmentioning
confidence: 99%